Total Productive Maintenance: implementation of the focused improvement pillar in a tertiary sector company - Goelzer, Diego Prati; Pizzolato, Morgana; Arenhart, Rodrigo Schons (Brazilian Journal of Production Engineering, 2026)
With the growing importance of the tertiary sector in the world economy, companies need alternatives to become competitive. Maintenance increases the efficiency and quality of the services provided. This study aimed to implement the Focused Improvement pillar of Total Productive Maintenance (TPM) within a tertiary sector company, specifically an automotive center specializing in tire replacement. The research methodology comprised four sequential phases: initial diagnostic, (2) kick-off and elimination of minor failures, identification of process failure modes and their effects, and determination of critical implementation factors. The Overall Equipment Effectiveness (OEE) was employed to quantitatively monitor process evolution, while the Failure Mode and Effects Analysis (FMEA) was conducted to define the criticality of process steps and establish preventive actions to block potential failure causes. Monitoring by indicator, the commitment of those involved, communication, and adaptation to the company’s context were critical factors in the implementation. In further studies, we recommend adopting a qualitative approach to investigate the effects on service quality and implementing other TPM pillars.